Impact of Equitization on Performance of Enterprises in Vietnam - Truong, Dong Loc (University of Economics Ho Chi Minh City, 2023)
The main objective of this study is to measure the impact of equitization on firm performance in Vietnam. The dataset, retrieved from the survey on enterprises conducted by the General Statistics Office of Vietnam (GSO), consists of 301 equitized state-owned firms and 127 unequitized state-owned firms during the period from 2007 to 2010. By using propensity score matching (PSM) combined with difference in differences (DID) approach, we find that equitization has positive impacts on the ratio of income before tax to total assets and the ratio of income before tax to sales. Moreover, this study reveals that debt ratio, total asset turnover, and the number of employees have significantly decreased after equitization. However, no evidence is found regarding the effect of equitization on productivity of equitized firms.